2016
DOI: 10.1002/2016gc006472
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the role of subsurface plumbing on geothermal discharge

Abstract: In order to better understand the diverse discharge styles and eruption intervals observed at geothermal features, we performed three series of laboratory experiments with differing plumbing geometries. A single, straight conduit that connects a hot water bath (flask) to a vent (funnel) can originate geyser‐like periodic eruptions, continuous discharge like a boiling spring, and fumarole‐like steam discharge, depending on the conduit length and radius. The balance between the heat loss from the conduit walls a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 60 publications
(118 reference statements)
1
21
0
Order By: Relevance
“…Laboratory studies have been used to show that steady heating and recharge can lead to episodic eruptions (Munby 1902, Forrester & Thune 1942, Steinberg et al 1982, to show how increasing complexity of plumbing geometries results in greater variation in discharge styles and eruption intervals (Namiki et al 2016), to understand the effects of geometry on convection and hence temperature in the conduit (Sherzer 1933), to show how increasing reservoir temperature increases the vigor of eruptions (Toramaru & Maeda 2013), to show how the decrease in reservoir pressure over the course of the eruption leads to recharge and the end of eruption (Lasic 2006), to show how bubble formation and collapse generates weak high-frequency tremors (Anderson et al 1978), and to show how intermittent modulation of the rate of boiling and the closely coupled accelerations and decelerations of the water column generate strong low-frequency tremors (Anderson et al 1978).…”
Section: Wwwannualreviewsorg • Dynamics Of Geyser Eruptionsmentioning
confidence: 99%
“…Laboratory studies have been used to show that steady heating and recharge can lead to episodic eruptions (Munby 1902, Forrester & Thune 1942, Steinberg et al 1982, to show how increasing complexity of plumbing geometries results in greater variation in discharge styles and eruption intervals (Namiki et al 2016), to understand the effects of geometry on convection and hence temperature in the conduit (Sherzer 1933), to show how increasing reservoir temperature increases the vigor of eruptions (Toramaru & Maeda 2013), to show how the decrease in reservoir pressure over the course of the eruption leads to recharge and the end of eruption (Lasic 2006), to show how bubble formation and collapse generates weak high-frequency tremors (Anderson et al 1978), and to show how intermittent modulation of the rate of boiling and the closely coupled accelerations and decelerations of the water column generate strong low-frequency tremors (Anderson et al 1978).…”
Section: Wwwannualreviewsorg • Dynamics Of Geyser Eruptionsmentioning
confidence: 99%
“…These studies show how seismic and geodetic measurements over a range of frequencies can be used to characterize the plumbing systems of, and pressures within, geysers. Additional imaging tools include using microphones (e.g., Namiki et al, ), forward looking infrared (e.g., Karlstrom et al, ), and ground‐penetrating radar to characterize the shallowest subsurface (e.g., Lynne et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a deeper and larger reservoir boils and evacuates in main eruptions with an interval strictly controlled by long-term recharge and heating rates. Significant pressure and temperature gradients might be present in a long and narrow conduit leading to variability in the preplay sequence (Namiki et al, 2016), whereas the larger reservoir is expected to be more uniform in thermodynamic state due to convection, resulting in a stable recurrence time for the main eruption. There are similarities among type-1, type-2 preplays, and main eruptions at LSG compared to small, medium, and large eruptions, respectively, observed in the Adelstein et al (2014) experiments.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
“…Here we use seismic signals recorded for 4 days by multiple broadband seismometers around Lone Star Geyser (LSG), Yellowstone National Park (Figure 1), to improve the understanding of multiphase fluid storage and transport, before, during and after eruptions. We build on previous geophysical investigations at LSG (Karlstrom et al, 2013; Namiki et al, 2016; Vandemeulebrouck et al, 2014). These studies revealed complex eruption cycles in which the main eruptions that occur every ~3 hr are preceded by a variable number of preplay episodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation